Upaya Pengurus Lembaga Pendidikan Dewasa Qiro’ati Dalam Membentuk Kader Guru Pada Peserta Didik di Tambakrejo Waru Sidoarjo - bagus malik alindra; Munawir (Universitas Yudharta Pasuruan, 2022)
Assessments are a common activity in the educational process. Assessments have a qualitative function in knowing the learning process experienced by students. Therefore, the assessment process is very necessary in education to measure the ability of students to absorb the learning process. The purpose of this study was to analyze the efforts of the management of the Qiro’ati adult education institution in forming a cadre of teachers for students in Tambakrejo Waru Sidoarjo. This study used a qualitative method with a descriptive approach. The object of this study is LPD Qiro’ati Tambakrejo Waru Sidoarjo. The informant of this study was the two informers, the builder and the chairman of LPD Qiro 'ati. The result of this study showed is an adjustment between the vision and the mission of the builder LPD and the chairman of the LPD in assessing the progress of students in each volume to the final stage, namely the examination process (tashih).